The Development of a Cooperative Learning Model Using Educandy for Vocabulary Instruction at State Islamic Primary School 1 South Tangerang - Elta Dwi Prasepti; Muhbib Abdul Wahab; Wati Susiawati (Al-Muyassar: Journal of Arabic Education, 2025)
The researcher selected this topic based on the need to develop a learning model that supports vocabulary acquisition and aligns with students' needs. Students face difficulties in learning vocabulary, such as the limited variety of instructional media, particularly technological tools, reliance on traditional methods, and low motivation, which hinder the optimal achievement of educational objectives. This study aims to explore the development process, validity, and effectiveness of a cooperative learning model, specifically the Teams Games Tournaments (TGT) type, utilizing Educandy for vocabulary instruction. The researcher employed the Research and Development (R&D) methodology, following the ADDIE model developed by Raiser and Molenda. This model consists of five phases: Analysis, Design, Development, Implementation, and Evaluation. The data collection instruments used in this study included tests (pre-test and post-test), questionnaires, interviews, and observations. For data analysis, the researcher applied the Likert scale and the N-Gain test. The findings indicated that the cooperative learning model of the Teams Games Tournaments type, integrated with Educandy, demonstrated a "very good" quality, receiving an evaluation score of 92% from the instructional media expert, 83.3% from the subject matter expert, and 77% from the Arabic language teacher. Furthermore, the results of the N-Gain test showed that the model's effectiveness was classified as "moderate effectiveness," with a score of 0.7. Keywords: Educandy, Cooperative Learning Model, Vocabulary. مستخلص البحثاختارت الباحثة هذا الموضوع على خل?ية البحث وهي الحاجة إلى تطوير نموذج التعلم الذي يدعم تعلم الم?ردات ويتناسب مع احتياجات الطلاب. يواجه الطلاب صعوبات ?ي تعلم الم?ردات، مثل قلة تنوع الوسائل التعليمية، خاصة التكنولوجية، والاعتماد على الأساليب التقليدية، وضع? الدا?عية، مما يعيق تحقيق الأهدا? التعليمية بشكل? أمثل. يهد? هذا البحث إلى الكش? عن عملية تطوير نموذج التعلم التعاوني، الذي يقتصر على نوع مسابقة ألعاب ال?ريق (Teams Games Tournaments)، باستخدام إيدوجاندي لتعليم الم?ردات، وصلاحيته، و?عاليته. استخدمت الباحثة ?ي هذا البحث منهج البحث والتطوير (Research and Development)  و?قًا لنموذج ADDIE  الذي طوّره Raiser و Molenda. يتكون هذا النموذج من خمس مراحل، وهي: التحليل، والتصميم، والتطوير، والتن?يذ، والتقييم. أما أدوات جمع البيانات المستخدمة ?ي هذا البحث، ?تشمل الاختبارات (الاختبار القبلي والبعدي)، والاستبيان، والمقابلة، والملاحظة. ولتحليل البيانات، استخدمت الباحثة مقياس ليكرت واختبار “N-Gain??. أظهرت نتائج البحث أن نموذج التعلم التعاوني من نوع مسابقة ألعاب ال?ريق القائم على وسيلة Educandy يتمتع بجودة "جيد جدا"، حيث حصل على تقييم بنسبة 92% من خبير الوسائل، و83.3% من خبيرة المواد، و77% من تقييم معلمة اللغة العربية. كما أظهرت نتائج اختبار N-Gain أن ?عالية النموذج تقع ?ي مستوى "ال?عالية المتوسطة" بدرجة 0.7. الكلمات الم?تاحية : إيدوجاندي، نموذج التعلم التعاوني، الم?ردات.